2020
DOI: 10.31234/osf.io/hm5at
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Character growth following collective life events: A study on perceived and measured changes in character strengths during the first wave of the COVID-19 pandemic

Abstract: Did the COVID-19 pandemic promote character growth? Studies using sequential samples suggested that collective life events can result in character growth, but their conclusions have been questioned. This study examined character growth during the COVID-crisis using three approaches (perceived changes in oneself and a closer other, and longitudinal analyses of changes). Additionally, it investigated the relationships between character strengths assessed before the pandemic, and well-being, compliance with regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In another context altogether, Gander and Wagner (2022) observed that character strengths measured up to 1.5 years before the first wave of the COVID-19 pandemic were associated with self-reported adaptive behavioral responses to the pandemic. For example, individuals higher on pre-COVID character strengths of judgment, perseverance, humility, and prudence self-reported greater compliance with national COVID regulations.…”
Section: A Personality Science Approach To the Study Of Post-traumati...mentioning
confidence: 99%
See 1 more Smart Citation
“…In another context altogether, Gander and Wagner (2022) observed that character strengths measured up to 1.5 years before the first wave of the COVID-19 pandemic were associated with self-reported adaptive behavioral responses to the pandemic. For example, individuals higher on pre-COVID character strengths of judgment, perseverance, humility, and prudence self-reported greater compliance with national COVID regulations.…”
Section: A Personality Science Approach To the Study Of Post-traumati...mentioning
confidence: 99%
“…Second, Gander and Wagner (2022) compared individuals’ perceptions of character trait changes with longitudinal changes in these characters traits before and after the first wave of the COVID-19 pandemic. Individuals reported changes in 21 of 24 character traits assessed when asked to retrospectively think if they had changed as a result of the pandemic, but pre-to-post pandemic change was only observed in humility and prudence when examined longitudinally.…”
Section: A Personality Science Approach To the Study Of Post-traumati...mentioning
confidence: 99%
“…Lau et al ( 2006 ), also, reported social growth during the SARS outbreak among Hong Kong residents. Furthermore, other positive changes such as appreciating life, improved ability to resist stress (Sun et al, 2021a ), lifestyle changes, and mental health awareness (Lau et al, 2006 ), character growth (Gander & Wagner, 2020 ), personal strength, new possibilities, and spiritual change (Kalaitzaki, 2020 ; Prieto-Ursúa & Jódar, 2020a , 2020b ) were observed among individuals during a pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since their theorization, character strengths' associations with several desirable outcomes have been studied (see Niemiec, 2013;Stahlmann & Ruch, 2020), ranging from positive functioning at work (Dubreuil et al, 2014;Harzer & Ruch, 2012, 2013, to flourishing interpersonal relationships (Goodman et al, 2018;Lavy et al, 2014), academic learning and satisfaction (Lounsbury et al, 2009), and personal growth Lavy & Littman-Ovadia, 2017;Peterson et al, 2008). Particular focus has been devoted to subjective well-being, and especially life satisfaction (Bruna et al, 2019) which has been used as the gold standard for external validity in almost every validation study of character strengths measures (e.g., VIA-IS measures)and there is a growing interest in their protective role against depressive symptoms and mental health issues (e.g., Gander & Wagner, 2020;Petkari & Ortiz-Tallo, 2018;Tehranchi et al, 2018).…”
Section: Character Strengths: a Field Ripe With Potentialmentioning
confidence: 99%